Research on Network Architecture for the Space-Integrated-Ground Information Network in 6G - Hui XU; Shaohui SUN (天地一体化信息网络)
The requirements and the fl exible and reconfi gurable network architecture for the space-integrated-ground information network was proposed based on analyzed the 6G network vision and challenges faced by the space-integrated-ground information network.Based on the proposed network architecture, the intelligent network management and control architecture and the virtualization technology of the space-integrated-ground information network were proposed to realized the dynamic confi gurability of the network.